Perancangan Media Pembelajaran Augmented Reality Menggunakan Metode User Centered Design pada Topik Energi - Daniel Rinaldi; Wisnu Juli Wiono; B. Anggit Wicaksono; Anggreini (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to develop an Augmented Reality (AR)-based learning media called EcoTurbine using the User-Centered Design (UCD) method and to evaluate its usability through the System Usability Scale (SUS). The research subjects were 77 senior high school students who had studied energy-related material and possessed basic smartphone skills. The development process followed the UCD stages, placing teachers and students at the center of the design to ensure that the resulting media aligned with user needs and characteristics. The evaluation yielded an average SUS score of 78.34, which falls within the acceptable category, with an adjective rating of good and grade C. These findings indicate that EcoTurbine is suitable as a supporting medium for biology learning on renewable energy topics, although limitations remain in terms of device compatibility and students’ initial adaptation to AR technology. This study provides empirical contributions by demonstrating the effectiveness of UCD in developing AR-based learning media and offering quantitative evidence of usability through SUS evaluation, which supports the enhancement of student engagement and motivation in learning.